THE QUALITY OF TUBERCULOSIS SERVICES IN PATIENTS’ PERSPECTIVES: A LITERATURE REVIEW - Aufiena Nur Ayu Merzistya; Mateus Sakundarno Adi; Dwi Sutiningsih; Sri Ratna Rahayu (Indonesian Journal of Health Administration, 2021)
Background: The assessment from the patient's perspective is the assurance of TB service’ quality to achieve the "End TB" target. The information regarding TB services’ quality assessment in the dimensions of QUOTE TB Light is not widely found.Aims: The study aims to review TB services' quality from the patients’ perspective in the 7 dimensions of QUOTE TB Light.Methods: This literature review study searched from 3 databases, namely PubMed, Science-Direct, and Google Scholar since July - October 2020. The inclusion criteria were research on TB services quality, patients’ perspective, and patient assessment of 7 dimenssion. Articles assessed the other health services’ quality and published before January 2015 was excluded.Results: A total of 7 from 89 articles found were selected for review. The patients’ assessments are based on their experiences or satisfactions. Most of the studies are satisfied with service availability, communication, patient-provider interactions, competence, and affordability. The patients’ dissatisfactions about infrastructure and stigma acquired during treatment.Conclusion: Infrastructure and stigma are assessed negatively. The continously evaluation and training for health workers need to be improved so they can serve patients well. The patients’ perspectives can be the major consideration for providers to enhance the TB services’ quality.Keywords: Quality of TB services, QUOTE TB Light, patients’ perspectives, Tuberculosis